Numerical Study of the Composite Effects of Uneven Street Canyons and Time-varying Inflows on the Air Flows and Pollutant Dispersion - Weijun Li; Yuanping He; Yunwei Zhang; Qingxiang Shui; Xinyi Wu; Chuck Wah. Yu; Zhaolin Gu (Aerosol and Air Quality Research, 2020)
Abstract The dispersion behavior of pollutants in realistic street canyons is dominated by the pattern of airflow, which is closely linked to the building layout and air inflow at the street canyon boundary. Although uneven building layouts and time-varying inflows have been individually investigated for their influence on air flow pattern and pollutant dispersion in street canyons, the combined effects of these two factors have not been examined. In this study, four street canyon models, one even and three uneven models with different occupying ratios of high-rise buildings, were numerically studied using large-eddy simulation under steady inflow and time-varying inflow conditions. The results showed that both the uneven building layouts and the time-varying inflow condition enhanced the air flow strength and pollutant removal efficiency inside the street canyon. However, the composite effects of these factors were not simply additive. The worst pollutant removal efficiency was observed for air flow in the even street canyon with the steady inflow, which is the typical benchmark case in studies. With the time-varying inflow, the induced updrafts prevented the relatively tall high-rise buildings from restricting the height of the pollutant dispersion during the inflow in the valley. The pattern of the pollutant isoconcentration plane and the time-series curves of normalized concentrations in the even and uneven street canyon models exhibited fluctuant features with the time-varying inflow.